The Qualified Mens Rea Model: Layered Culpability in General Commodity Smuggling Offenses Implicating Corruption - R. Bayu Probo Sutopo; John Pieris; Aarce Tehupeiory; Hulman Panjaitan (SIGn Jurnal Hukum, 2026)
The national criminal justice system continues to face difficulties in proving criminal intent (mens rea) in general commodity smuggling offenses that are normatively connected to corruption offenses. These difficulties arise when the proof of culpability is directed solely at the individual mental state. In contrast, modern economic offenses are often committed through corporations, sequences of goods transportation activities, customs documentation management, and the exercise of official authority. This study aims to develop an instrument to evaluate the culpability of state apparatuses and corporate entities proportionately, without exceeding the principle of legality. This study employs normative legal research using a statute approach, a conceptual approach, and a limited comparative approach. Comparative legal doctrines, such as corporate recklessness, the responsible corporate officer doctrine, conscious disregard of substantial risk, and willful blindness, are used as conceptual instruments rather than as direct bases for criminal punishment. The findings show that the Qualified Mens Rea Model can be constructed as a layered evaluative framework comprising subjective, normative, corporate-functional, and corruption-functional dimensions. The model is then operationalized as a Layered Evidentiary Mechanism Matrix that situates Law Number 17 of 2006, Law Number 20 of 2001, and Law Number 1 of 2023 within an interrelated normative framework. This study concludes that the model can assist judges in more accurately distinguishing general commodity smuggling offenses, abuse of authority, office-related bribery, and lawful policy discretion.